The Impact of ISO 9000 Certification to the Organization Performance - Siaw, Ching Foon (1998)
ISO 9000 Standards have become an important tool for an organization to enhance its market share in both local and overseas market. However, little empirical studies have been conducted to determine the impact of ISO 9000 certification on the financial performance of the company. In this study, a survey questionnaire has been designed to collect some information from the quality assurance personnel through telephone interviews. On the hand, company financial data was gathered to analyze the relationships of the ISO 9000 certification and the company financial performance. Descriptive statistics namely frequencies, percentage and mean were used in describing the some of the finding. In addition, simple regression analysis was carried out to analyze the significance of ISO 9000 certification on the financial performance of the company. Findings showed that the companies registered with ISO 9000 were mainly driven by external forces, such as market trend and statutory requirements. The study also found that the most quality assurance personnel perceived that they gained all the benefits (competitive edge) after pursuing ISO 9000 certification. However, the profitability ratio analysis did not support such conclusion. It revealed that the business performance of a company have indicated a declining trend instead of improvement after achieving ISO 9000 certification status. This study also highlighted the necessity of Total Quality Management in a company and the integration of both in order to achieve the ultimate goal of the company.